Pacific Biological Laboratory - Unknown:::Creator::::::::::::
The Original building of Pacific Biological Laboratories, 740 Ocean View Avenue (later 800 Cannery Row,) to which Ed Rickett's moved in 1928. This building burned down on November 25th, 1936.